A method for detecting concentration of magnetic nanomaterials

The concentration of magnetic nanomaterials is detected by the ST-FMR device, and the damping factor changes in the ST-FMR device are used to accurately detect the low concentration of magnetic nanomaterials, solving the problem that the existing technology is difficult to detect the concentration of trace magnetic nanomaterials. With high sensitivity and low detection cost.

CN114646909BActive Publication Date: 2025-02-14BEIJING NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210274448.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-21
Publication Date
2025-02-14
Estimated Expiration
2042-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect trace concentrations of magnetic nanomaterials, especially in the range of ≤0.5 mg/mL.

Method used

The concentration of magnetic nanomaterials is detected by using ST-FMR device. By dropping the solution to be tested to the surface of the ST-FMR device, a series of microwave current is passed, and the DC voltage signal is detected under the action of the applied magnetic field to obtain the rectified voltage-applied magnetic field curve. , and the resonance line width and damping factor were obtained by fitting, and the concentration of magnetic nanomaterials was quantitatively detected by combining the concentration-damping factor standard linear curve.

Benefits of technology

Accurate detection of low concentration of magnetic nanomaterials (≤0.5mg/mL), high sensitivity, simple operation and low detection cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114646909B_ABST
    Figure CN114646909B_ABST
Patent Text Reader

Abstract

The present invention provides a method for detecting the concentration of magnetic nanomaterials, and relates to the technical field of detecting trace magnetic nanomaterials. In the process of detecting the concentration of magnetic nanomaterials by using the spin-torque ferromagnetic resonance (ST-FMR) technology, a microwave current is introduced into the SOT source layer along the X direction to generate a spin current perpendicular to the plane direction of the film, which acts on the magnetic moment of the adjacent ferromagnetic layer to generate a torque, causing it to precess. When the magnetic nanomaterial is dripped onto the surface of the ferromagnetic layer film, the resonance condition during the ST-FMR test is affected, so that the damping factor of the system increases with the increase in the amount of magnetic nanomaterials, thereby achieving quantitative and accurate detection of low-concentration (≤0.5 mg / mL) magnetic nanomaterial solutions. The method has low testing cost, short detection time, and high detection sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of detecting trace magnetic nano materials, and in particular to a method for detecting the concentration of magnetic nano materials. Background Art

[0002] Magnetic nanomaterials have special properties such as surface effect, small size effect, quantum effect, good magnetic induction at room temperature and biocompatibility. They are widely used in green energy, biotherapy, environmental monitoring, medical imaging and other fields. As magnetic nanomaterials play an increasingly important role in human health and environmental protection, the effects they play in various systems are often closely related to their concentrations. For example, the concentrations of magnetic nanomaterials in targeted therapy during biotherapy and magnetic nanocatalyst materials at the cathode and anode of fuel cells are usually extremely small and difficult to detect. Therefore, it is very important to detect the concentration of magnetic nanomaterials.

[0003] Currently, the concentration of magnetic nanomaterials is mainly tested by superconducting quantum interference device or vibrating sample magnetometer. However, the above test methods are difficult to test the trace concentration (≤0.5 mg / mL) of magnetic nanomaterials in the solution. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for detecting the concentration of trace magnetic nanomaterials. The detection method provided by the present invention can detect the trace concentration of magnetic nanomaterials.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for detecting the concentration of a magnetic nanomaterial, comprising the following steps:

[0007] The magnetic nanomaterial solution to be tested is dripped onto the surface of the ST-FMR device, a series of microwave currents are introduced, and a DC voltage signal is detected by a lock-in amplifier under the action of an external magnetic field to obtain a rectified voltage-external magnetic field curve; the frequency of the microwave current is ≤20GHz; the ST-FMR device comprises a magnetic multilayer film material, and the magnetic multilayer film material comprises a base layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence;

[0008] The rectified voltage-external magnetic field curve is fitted according to formula (1) to obtain a series of resonance line widths;

[0009]

[0010] In the formula (1), V mix is the DC voltage signal value, V ais the intensity of the peak of the antisymmetric fitting curve, V s is the peak intensity of the symmetrical fitting curve, ΔH is the resonance line width, and H r is the position of the resonance peak, H is the strength of the external magnetic field;

[0011] The series resonance line width and the frequency of the microwave current are fitted according to formula (2) to obtain the damping factor;

[0012]

[0013] In the formula (2), ΔH is the resonance line width, α is the damping factor, γ is the gyromagnetic ratio, ΔH0 is the extrinsic line width, and f is the frequency of the microwave current;

[0014] The concentration of the magnetic nanomaterial solution to be tested is obtained according to the damping factor and the concentration-damping factor standard linear curve.

[0015] Preferably, the method for obtaining the concentration-damping factor standard linear curve comprises the following steps:

[0016] A series of magnetic nanomaterial solutions with different concentrations are respectively added dropwise to the surface of the ST-FMR device, and a series of microwave currents with different frequencies are introduced to obtain a series of rectified voltage-external magnetic field curves; the frequency of the microwave current is ≤20 GHz;

[0017] The series of rectified voltage-external magnetic field curves are fitted according to the formula (1) to obtain a series of resonance line widths;

[0018] The series of resonance line widths and the frequency of the microwave current are fitted according to the formula (2) to obtain a concentration-damping factor standard linear curve.

[0019] Preferably, the ST-FMR device also includes a first electrode 6 and a second electrode 7 arranged on opposite sides of the magnetic multilayer film material 5, a phase-locked amplifier 9 connected to the first electrode, a coupler 8 electrically connected to the first electrode 6 and the phase-locked amplifier 9, and an external magnetic field device 10 arranged between the first electrode 6 and the second electrode 7; the second electrode 7 is grounded.

[0020] Preferably, the material of the SOT source layer includes heavy metal or a material having a spin Hall effect.

[0021] Preferably, the heavy metal includes one or more of Pt, Ta, W, Au and Hf.

[0022] Preferably, the material having the spin Hall effect includes one or more of MoS2, WTe2, PtTe2, Bi2Te3 and Fe3GeTe2.

[0023] Preferably, the material of the ferromagnetic layer includes one or more of Fe, Co, CoNi, NiFe(Py), FePt and CoFeB.

[0024] Preferably, the thickness of the SOT source layer and the ferromagnetic layer are independently 5-10 nm.

[0025] Preferably, the material of the protective layer includes one or more of MgO, SiO2, Ru, W, and Ta;

[0026] The thickness of the protective layer is ≤10 nm.

[0027] Preferably, the material of the base layer includes one or more of single crystal Si, MgO and SiO2.

[0028] The invention provides a method for detecting the concentration of a magnetic nano material, comprising the following steps: dripping a magnetic nano material solution to be tested onto the surface of an ST-FMR device, passing a series of microwave currents, detecting a DC voltage signal through a phase-locked amplifier under the action of an external magnetic field, and obtaining a rectified voltage-external magnetic field curve; the frequency of the microwave current is ≤20 GHz; the ST-FMR device comprises a magnetic multilayer film material, and the magnetic multilayer film material comprises a substrate layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence; fitting the rectified voltage-external magnetic field curve according to formula (1) to obtain a series of resonance line widths; fitting the series of resonance line widths and the frequency of the microwave current according to formula (2) to obtain a damping factor; and obtaining the concentration of the magnetic nano material solution to be tested according to the damping factor and a concentration-damping factor standard linear curve. The present invention utilizes the ST-FMR device (spin torque-ferromagnetic resonance device) detection process, the SOT source layer in the magnetic multilayer film material has a spin-orbit torque effect (SOT effect), when the current is passed in the X direction of the magnetic multilayer film material, a spin polarized current along the Y direction can be generated, and accumulated at the interface, a spin current is generated in the Z direction, and injected into the adjacent ferromagnetic layer, the magnetic moment of the ferromagnetic layer precesses under the torque generated by the spin current, and the dynamic change of the magnetic moment in the ferromagnetic layer can be detected by the spin torque ferromagnetic resonance technology; when the magnetic nano material is dripped onto the surface of the ferromagnetic layer film, the resonance condition during the ST-FMR test is affected, so that the damping factor of the system increases with the increase in the amount of magnetic nano material. Based on this principle, by changing the concentration of the magnetic nano material solution, the quantitative and accurate detection of the magnetic nano material solution with low concentration (≤0.5mg / mL) can be achieved through the change of the damping factor in the ST-FMR device based on the magnetic multilayer film material, and the detection sensitivity is high. Moreover, the detection method provided by the present invention is simple to operate and has low detection cost.

[0029] Further, in the process of detecting the concentration of magnetic nano material solution by ST-FMR device, the first electrode current can induce an oscillating spin current at the boundary of magnetic nano material, and the spin current acts on the ferromagnetic layer to make its magnetization precess near the effective field. The DC voltage signal from the device sample to be tested is measured by a phase-locked amplifier. The DC voltage signal is generated by the anisotropic magnetoresistance of the ST-FMR device itself and the microwave current coupling. By analyzing and fitting the change of DC voltage, the key parameter of the spin-orbit moment (SOT) effect on the magnetic moment of the ferromagnetic layer, the damping factor, can be obtained. Since the magnetic moment of the magnetic nano material particles themselves produces a certain disturbance to the magnetic moment precession of the magnetic multilayer film, the resonance condition is affected, so that the damping factor increases with the increase of the amount of magnetic nano material. Based on this principle, by changing the concentration of the magnetic nano material solution, the quantitative and accurate detection of low-concentration magnetic nano material solution can be achieved through the change of the damping factor in the ST-FMR device. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the structure of the multilayer film material of the ST-FMR device, wherein 1 is a protective layer, 2 is a ferromagnetic layer, 3 is a SOT source layer, and 4 is a substrate layer;

[0031] Figure 2 Schematic diagram of the structure of the ST-FMR device, wherein 6 is a first electrode and 7 is a second electrode;

[0032] Figure 3 Schematic diagram of the measurement of ST-FMR device, wherein 1 is a protective layer, 2 is a ferromagnetic layer, 3 is a SOT source layer, 4 is a substrate layer, 5 is a magnetic multilayer film material, 6 is a first electrode, 7 is a second electrode, 8 is a coupler, 9 is a lock-in amplifier, and 10 is an external magnetic field device;

[0033] Figure 4 Schematic diagram of a magnetic nanomaterial solution dripped onto the surface of a magnetic multilayer film material, wherein 1 is a protective layer, 2 is a ferromagnetic layer, 3 is a SOT source layer, 4 is a base layer, and 11 is a magnetic nanomaterial;

[0034] Figure 5 The result diagram of the series of ST-FMR curves, where the inset is a partial enlarged diagram of the series of ST-FMR curves;

[0035] Figure 6 This is the standard linear curve of concentration-damping factor.

[0036] Figure 7 The distribution diagram of magnetic nanomaterials with different concentrations on the ST-FMR device under a scanning electron microscope. DETAILED DESCRIPTION

[0037] The present invention provides a method for detecting the concentration of a magnetic nanomaterial, comprising the following steps:

[0038] The magnetic nanomaterial solution to be tested is dripped onto the surface of the ST-FMR device, a series of microwave currents are introduced, and a DC voltage signal is detected by a lock-in amplifier under the action of an external magnetic field to obtain a rectified voltage-external magnetic field curve; the frequency of the microwave current is ≤20GHz; the ST-FMR device comprises a magnetic multilayer film material, and the magnetic multilayer film material comprises a base layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence;

[0039] The rectified voltage-external magnetic field curve is fitted according to formula (1) to obtain a series of resonance line widths;

[0040]

[0041] In the formula (1), V mix is the DC voltage signal value, V a is the intensity of the peak of the antisymmetric fitting curve, V s is the peak intensity of the symmetrical fitting curve, ΔH is the resonance line width, and H r is the position of the resonance peak, H is the strength of the external magnetic field;

[0042] The series resonance line width and the frequency of the microwave current are fitted according to formula (2) to obtain the damping factor;

[0043]

[0044] In the formula (2), ΔH is the resonance line width, α is the damping factor, γ is the gyromagnetic ratio, ΔH0 is the extrinsic line width, and f is the frequency of the microwave current;

[0045] The concentration of the magnetic nanomaterial solution to be tested is obtained according to the damping factor and the concentration-damping factor standard linear curve.

[0046] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0047] The present invention drips a magnetic nano material solution to be tested onto the surface of an ST-FMR device, passes a series of microwave currents, and detects a DC voltage signal through a lock-in amplifier under the action of an external magnetic field to obtain a rectified voltage-external magnetic field curve (ST-FMR curve); the frequency of the microwave current is ≤20GHz; the ST-FMR device comprises a multilayer thin film material, and the magnetic multilayer film material comprises a base layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence.

[0048] In the present invention, the magnetic nanomaterial in the magnetic nanomaterial solution to be tested preferably includes magnetic nanomaterials containing one or more of Co, Ni and Fe, more preferably includes one or more of PtCo, PtNi, CoNi, PtCoMn, PtNiMn, PtCoCr and PtFe, and further preferably is PtCo, PtNi, CoNi, PtCoMn, PtNiMn, PtCoCr or PtFe.

[0049] In the present invention, the ST-FMR device comprises a multilayer thin film material, wherein the multilayer thin film material comprises a base layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence. In the present invention, the structural schematic diagram of the multilayer thin film material is as shown in Figure 1 As shown, 1 is a protective layer, 2 is a ferromagnetic layer, 3 is a SOT source layer, and 4 is a substrate layer.

[0050] In the present invention, the material of the base layer preferably includes one or more of single crystal Si, MgO and SiO2, and more preferably single crystal Si, MgO or SiO2. The present invention has no special limitation on the thickness of the base layer, and a thickness well known to those skilled in the art can be used, such as 0.5 mm.

[0051] In the present invention, the material of the SOT source layer includes heavy metals or materials having a spin Hall effect. In the present invention, the heavy metal preferably includes one or more of Pt, Ta, W, Au and Hf, and more preferably includes Pt, Ta, W, Au or Hf.

[0052] In the present invention, the material having the spin Hall effect includes one or more of MoS2, WTe2, PtTe2, Bi2Te3 and Fe3GeTe2, and more preferably includes MoS2, WTe2, PtTe2, Bi2Te3 or Fe3GeTe2. In the present invention, the thickness of the SOT source layer is preferably 5 to 10 nm, more preferably 6 to 9 nm, and further preferably 7 to 8 nm.

[0053] In the present invention, the material of the ferromagnetic layer preferably includes one or more of Fe, Co, CoNi, NiFe, FePt and CoFeB, and more preferably includes Fe, Co, CoNi, NiFe, FePt or CoFeB. In the present invention, the thickness of the ferromagnetic layer is preferably 5 to 10 nm, more preferably 6 to 9 nm, and further preferably 7 to 8 nm.

[0054] In the present invention, the material of the protective layer preferably includes one or more of MgO, SiO2, Ru and Ta, and more preferably includes MgO, SiO2, Ru or Ta. In the present invention, the thickness of the protective layer is preferably ≤10nm, more preferably 1 to 10nm, and further preferably 2 to 5nm.

[0055] The present invention has no special limitation on the preparation method of the magnetic multilayer film material, and any preparation method familiar to those skilled in the art may be used, such as magnetron sputtering, electron beam evaporation, molecular beam epitaxy or chemical vapor deposition.

[0056] In the present invention, the ST-FMR device preferably further comprises a first electrode 6 and a second electrode 7 disposed on opposite sides of the multilayer thin film material 5, a lock-in amplifier 9 electrically connected to the first electrode 6, a coupler 8 electrically connected to the first electrode 6 and the lock-in amplifier 9, and an external magnetic field device 10 disposed between the first electrode 6 and the second electrode 7; the second electrode 7 is grounded. In the present invention, the structural schematic diagram of the ST-FMR device is as follows Figure 2 and Figure 3 As shown, 1 is a protective layer, 2 is a ferromagnetic layer, 3 is a SOT source layer, 4 is a substrate layer, 6 is a first electrode, and 7 is a second electrode. In the present invention, the materials of the first electrode and the second electrode independently preferably include Pt or Au. In the present invention, the external magnetic field device preferably includes a magnet. In the present invention, the function of the coupler is to filter the microwave current. First, a capacitor (passing AC and blocking DC) is used to inject microwave current into the sample, and then a DC signal is input into the phase-locked amplifier through a coil (passing DC and blocking AC).

[0057] In the present invention, the concentration of the magnetic nanomaterial solution to be tested is preferably 0.01 to 1 mg / mL, more preferably 0.01 to 0.5 mg / mL.

[0058] In the present invention, the frequency of the microwave current is preferably ≤20 GHz, more preferably 1-20 GHz, and further preferably 2-8 GHz; the power of the current is preferably 1-30 dBm, more preferably 5-25 dBm, and further preferably 10-20 dBm.

[0059] In the present invention, the angle between the microwave current and the direction of the external magnetic field provided by the external magnetic field device is preferably 0 to 180°, more preferably 30 to 120°, and further preferably 45°.

[0060] After obtaining the rectified voltage-external magnetic field curve, the present invention fits the rectified voltage-external magnetic field curve according to formula (1) to obtain a series of resonance line widths.

[0061] In the present invention, the formula (1) is:

[0062]

[0063] In the formula (1), V mix is the DC voltage signal value, V a is the intensity of the peak of the antisymmetric fitting curve, V s is the peak intensity of the symmetrical fitting curve, ΔH is the resonance line width, and H r is the position of the resonance peak, H is the strength of the external magnetic field;

[0064] The present invention has no special limitation on the fitting, and any fitting method well known to those skilled in the art may be used.

[0065] After obtaining the series resonance line width, the present invention fits the series resonance line width and the frequency of the microwave current according to formula (2) to obtain the damping factor;

[0066]

[0067] In the formula (2), ΔH is the resonance line width, α is the damping factor, γ is the gyromagnetic ratio, D is the extrinsic line width, and f is the frequency of the microwave current;

[0068] The present invention has no special limitation on the fitting, and any fitting method well known to those skilled in the art may be used.

[0069] After the damping factor is obtained, the present invention obtains the concentration of the magnetic nano material solution to be tested according to the damping factor and a concentration-damping factor standard linear curve.

[0070] In the present invention, the method for obtaining the concentration-damping factor standard linear curve preferably comprises the following steps:

[0071] A series of magnetic nanomaterial solutions with different concentrations are respectively added dropwise to the surface of the ST-FMR device, and a series of microwave currents with different frequencies are introduced to obtain a series of rectified voltage-external magnetic field curves; the frequency of the microwave current is ≤20 GHz;

[0072] The series of rectified voltage-external magnetic field curves are fitted according to the formula (1) to obtain a series of resonance line widths;

[0073] The series of resonance line widths and the frequency of the microwave current are fitted according to the formula (2) to obtain a concentration-damping factor standard linear curve.

[0074] The present invention drips a series of concentrations of magnetic nanomaterial solutions onto the surface of the ST-FMR device, and passes a series of microwave currents of frequencies to obtain a series of rectified voltage-external magnetic field curves; the frequency of the microwave current is ≤20GHz. In the present invention, the ST-FMR device is the same as the aforementioned ST-FMR device, and will not be repeated here. In the present invention, the concentrations of the series of concentrations of magnetic nanomaterial solutions are preferably 0mg / mL, 0.1mg / mL, 0.2mg / mL, 0.3mg / mL, 0.4mg / mL and 0.5mg / mL. In the present invention, the frequency of the microwave current is preferably 2-8GHz, and is specifically preferably 2GHz, 3GHz, 4GHz, 5GHz, 6GHz, 7GHz and 8GHz; the power of the microwave current is preferably 1-30dbm, more preferably 5-25dbm, and further preferably 10-20dbm. In the present invention, the angle between the microwave current and the direction of the external magnetic field provided by the external magnetic field device is preferably 0-180°, more preferably 30-120°, and further preferably 45°.

[0075] After obtaining a series of rectified voltage-external magnetic field curves, the present invention fits the series of rectified voltage-external magnetic field curves according to the formula (1) to obtain a series of resonance line widths. The present invention has no special limitation on the fitting, and a fitting method well known to those skilled in the art can be used.

[0076] After obtaining the series of resonance line widths, the present invention fits the series of resonance line widths and the frequency of the microwave current according to the formula (2) to obtain a concentration-damping factor standard linear curve. The present invention has no special limitation on the fitting, and a fitting method familiar to those skilled in the art can be used. In the present invention, taking a PtCo magnetic nanomaterial with a diameter of about 10 nm as an example, the concentration-damping factor standard linear curve is shown in formula (3):

[0077] α=0.00164C+0.00308 Formula (3);

[0078] In the formula (3), C is the concentration of the PtCo magnetic nano material solution. In the present invention, the principle of detecting the concentration of magnetic nano materials by the ST-FMR device is utilized, and the detection of the concentration of trace magnetic nano materials is realized according to the different response degrees of the ST-FMR device to trace magnetic nano materials of different concentrations, specifically as follows: the magnetic nano material sample to be tested and the magnetic field generated by the external magnetic field device (such as a magnet) are placed in the same plane, a microwave current is passed through the first electrode, and under the action of the microwave current, an oscillating spin current is induced at the boundary of the SOT source layer, and the spin current acts on the ferromagnetic layer to make its magnetization intensity precess near the effective field, and the precession is also affected by the magnetic field generated by the magnetic nano material itself on the surface of the device, and a DC voltage signal from the overall device to be tested is detected by a lock-in amplifier, and the DC voltage signal is generated by the anisotropic magnetoresistance of the ST-FMR device itself and the microwave current coupling, and the key parameter of the spin-orbit moment (SOT) effect on the magnetic moment of the ferromagnetic layer, namely the damping factor, can be obtained by analyzing and fitting the change of the DC voltage. Since the magnetic moment of the magnetic nano material particles themselves produces a certain disturbance to the magnetic moment precession of the ferromagnetic layer, the resonance condition is affected, so that the damping factor of the test system increases with the increase of the concentration of the magnetic nano material. Based on this principle, the concentration of different magnetic nano materials can be tested, and the change of the damping factor in the ST-FMR device can be used to quantitatively measure the concentration. The method of testing the concentration of magnetic nano materials using the above-mentioned ST-FMR device of the present invention has a very high sensitivity and can be used to study the changes in the weak magnetic behavior of the surface of the magnetic multilayer film.

[0079] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0080] Example 1

[0081] The magnetic multilayer film material composition is as follows: the base layer is single crystal Si; the SOT source layer is Pt with a thickness of 5 to 10 nm; the ferromagnetic layer is NiFe alloy with a thickness of 5 to 10 nm; and the protective layer is Ru with a thickness of 2 nm.

[0082] 1uL of a series of PtCo magnetic nanomaterial solutions with concentrations of 0 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, and 0.4 mg / mL was dropped onto the surface of the magnetic multilayer film material, respectively, and a microwave current with a power of 15 dbm and a frequency of 2 GHz, 3 GHz, 4 GHz, 5 GHz, 6 GHz, 7 GHz, and 8 GHz was introduced in the X direction, and the angle between the microwave current and the applied magnetic field was 45°, to obtain a series of ST-FMR curves, and the series of ST-FMR curves were fitted according to the formula (1) to obtain a series of resonance line widths;

[0083] The series resonance line width and the frequency of the microwave current are fitted according to the formula (2) to obtain a concentration-damping factor standard linear curve, which is: α=0.00164C+0.00308;

[0084] 1 μL of a magnetic nanomaterial solution to be tested with a concentration of 0.5 mg / mL is dropped onto the surface of a magnetic multilayer film material, and a microwave current with a power of 15 dbm and frequencies of 2 GHz, 3 GHz, 4 GHz, 5 GHz, 6 GHz, 7 GHz and 8 GHz is introduced in the X direction to obtain an ST-FMR curve. The ST-FMR curve is fitted according to the formula (1) to obtain a series of resonance line widths; the series of resonance line widths and the frequency of the microwave current are fitted according to the formula (2) to obtain a damping factor; the damping factor is substituted into the concentration-damping factor standard linear curve to obtain a concentration of the magnetic nanomaterial solution to be tested of about 0.5 mg / mL, which is close to the actual solution concentration.

[0085] Figure 4 This is a schematic diagram of the magnetic nanomaterial solution being dropped onto the surface of the magnetic multilayer film material.

[0086] Figure 5 The results of the series of ST-FMR curves are shown in Figure 1, where the inset is a partial enlarged view of the series of ST-FMR curves. Figure 5 It can be seen that with the increase of the concentration of magnetic nanomaterials on the surface of the ST-FMR device, the resonance line width gradually increases and the position of the resonance peak gradually shifts to the right, indicating that the magnetic nanomaterials on the device surface affect the resonance state of the magnetic moment in the ferromagnetic layer during the test.

[0087] Figure 6 is the standard linear curve of concentration-damping factor. Figure 6 It can be seen that the concentration of magnetic nanomaterials and the damping factor show a monotonically increasing relationship curve. This is because during the ST-FMR test, the magnetic moment of the magnetic nanomaterial particles themselves produced a certain disturbance on the magnetic moment precession of the magnetic multilayer film, affecting the resonance conditions. Therefore, the damping factor of the system increases with the increase of the concentration of magnetic nanomaterials.

[0088] In order to more intuitively demonstrate the amount of magnetic nanomaterials on the ST-FMR device, the distribution of magnetic nanomaterials with different concentrations on the device surface was observed using a scanning electron microscope. Figure 7 The distribution diagram of magnetic nanomaterials with different concentrations on the ST-FMR device under a scanning electron microscope. Figure 7 It can be seen that the distribution of magnetic nanomaterials of different concentrations on the ST-FMR device under an electron microscope is consistent with the test results in Example 1. The amount of magnetic nanomaterials on the device surface increases with the increase in the concentration of the dripped liquid. Based on this principle and phenomenon, the concentration of magnetic nanomaterials is quantitatively measured by the different responses of the damping factor of the ST-FMR device to different concentrations of magnetic nanomaterials.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for detecting the concentration of a magnetic nanomaterial, comprising the following steps: The magnetic nanomaterial solution to be tested is dripped onto the surface of the ST-FMR device, a series of microwave currents are introduced, and a DC voltage signal is detected by a lock-in amplifier under the action of an external magnetic field to obtain a rectified voltage-external magnetic field curve; the frequency of the microwave current is ≤20GHz; the ST-FMR device comprises a magnetic multilayer film material, and the magnetic multilayer film material comprises a base layer, a SOT source layer, a ferromagnetic layer and a protective layer stacked in sequence; The rectified voltage-external magnetic field curve is fitted according to formula (1) to obtain a series of resonance line widths; In the formula (1), V mix is the DC voltage signal value, V a is the intensity of the peak of the antisymmetric fitting curve, V s is the peak intensity of the symmetrical fitting curve, ΔH is the resonance line width, and H r is the position of the resonance peak, H is the strength of the external magnetic field; The series resonance line width and the frequency of the microwave current are fitted according to formula (2) to obtain the damping factor; In the formula (2), ΔH is the resonance line width, α is the damping factor, γ is the gyromagnetic ratio, ΔH0 is the extrinsic line width, and f is the frequency of the microwave current; The concentration of the magnetic nanomaterial solution to be tested is obtained according to the damping factor and the concentration-damping factor standard linear curve.

2. The detection method according to claim 1, characterized in that: The method for obtaining the concentration-damping factor standard linear curve comprises the following steps: A series of magnetic nanomaterial solutions with different concentrations are respectively added dropwise to the surface of the ST-FMR device, and a series of microwave currents with different frequencies are introduced to obtain a series of rectified voltage-external magnetic field curves; the frequency of the microwave current is ≤20 GHz; The series of rectified voltage-external magnetic field curves are fitted according to the formula (1) to obtain a series of resonance line widths; The series of resonance line widths and the frequency of the microwave current are fitted according to the formula (2) to obtain a concentration-damping factor standard linear curve.

3. The detection method according to claim 1 or 2, characterized in that: The ST-FMR device comprises a first electrode (6) and a second electrode (7) arranged on opposite sides of the magnetic multilayer film material (5), a lock-in amplifier (9) connected to the first electrode, a coupler (8) electrically connected to the first electrode (6) and the lock-in amplifier (9), and an external magnetic field device (10) arranged between the first electrode (6) and the second electrode (7); the second electrode (7) is grounded.

4. The detection method according to claim 1, characterized in that: The material of the SOT source layer includes heavy metal or a material having a spin Hall effect.

5. The detection method according to claim 4, characterized in that: The heavy metal includes one or more of Pt, Ta, W, Au and Hf.

6. The detection method according to claim 4, characterized in that: The material having the spin Hall effect includes one or more of MoS2, WTe2, PtTe2, Bi2Te3 and Fe3GeTe2.

7. The detection method according to claim 1, wherein the material of the ferromagnetic layer comprises one or more of Fe, Co, CoNi, NiFe, FePt and CoFeB.

8. The detection method according to any one of claims 1, 4, 5, 6 or 7, characterized in that: The thickness of the SOT source layer and the ferromagnetic layer are independently 5-10 nm.

9. The detection method according to claim 1, characterized in that: The material of the protective layer includes one or more of MgO, SiO2, Ru, W, and Ta; The thickness of the protective layer is ≤10 nm.

10. The detection method according to claim 1 or 9, characterized in that: The material of the base layer includes one or more of single crystal Si, MgO and SiO2.

Citation Information

Patent Citations

  • Method for measuring exchange stiffness at a patterned device level

    CN108333539A

  • Perpendicular spin torque oscillator FMR frequency measurement method

    US20130069626A1